Analysis of the Prospect of China's Cold-Chain Logistics Development - Wang, Guohua; Bi, Chuanchen (Technium Social Sciences Journal, 2022)
With the rising of China's fresh food e-commerce industry, the steady-state growth of the market scale, the improvement of the consuming ability, the reinforcement of the country's management of food safety, the increase of the requirement of the downstream application of cold chain logistics, traditional refrigerated transport can't meet the requirement of the market in various aspects such as organization, management, equipment, facilities, information services, etc. and the cold-chain transportation industry requires upgrade, which promotes China's cold-chain logistics transportation industry to enter a period of rapid development. This paper applies the PESTE model to analyze the differences of cold-chain logistics in China and in developed countries and the development status of China's cold-chain logistics, and uses the literature review to analyze the development prospect of China's cold-chain logistics in the future.